Penggunaan Terapi Relaksasi Benson Kombinasi Aromaterapi Lavender pada Ibu dengan Nyeri Akut Post Sectio Caesarae di RS. Bhayangkara Bandar Lampung Tahun 2025 - Zulhaida; Wandini, Riska; Andoko (Jurnal Keperawatan Muhammadiyah, 2025)
Background: The Global Survey on Maternal and Perinatal Health shows that 46.1% of all births are by Caesarean section (CS). The number of deliveries by Caesarean section (CS) in Indonesia is 17.6%. The Lampung Provincial Health Office reported that the 2023 C-section rate was 26.56%. Meanwhile, at Bhayangkara Hospital in 2024, there were 204 mothers. C-section deliveries can cause several complications, including pain in the incision area or tearing of the abdominal wall and uterine tissue. Pain management therapies include Benson relaxation breathing techniques and aromatherapy. Objective: This study provides nursing care for post-C-section mothers using Benson Relaxation Therapy and Lavender Aromatherapy. Method: This final project report used a pure experimental research design with a pretest-posttest control group. The subjects were two women experiencing acute pain. The combination of lavender aromatherapy and Benson relaxation was applied once every two days. Pain levels were measured before and after non-pharmacological therapy was administered. During the study, the researchers used standard operating procedures. Results: The author conducted acute pain management using Benson relaxation therapy and lavender aromatherapy for 3 days on cesarean section (CS) patients. The acute pain in Mrs. S and Mrs. F was significantly reduced compared to Mrs. L and Mrs. A, with Mrs. S receiving a pain scale of 3 and Mrs. F receiving a pain scale of 2, compared to Mrs. L and Mrs. A receiving a pain scale of 4. This demonstrates the effectiveness of Benson relaxation therapy and lavender aromatherapy in reducing pain in cesarean section (CS) patients compared to no Benson relaxation therapy and lavender aromatherapy. Conclusion: The effectiveness of Benson relaxation therapy and lavender aromatherapy in reducing pain in cesarean section (CS) patients was demonstrated.